Determination of the Nitrogen to Protein Conversion Factor in Eggs of Coturnix Coturnix L. (Japanese Quail) [Determinación del Factor: De Conversión de Nitrógeno a Proteína en Huevos de Coturnix Coturnix L. (Codorniz Japonesa)] - Martinez-Salinas, J; Rios-Ramirez, M (Venezuelan Society of Pharmacology and Clinical and Therapeutic Pharmacology, 2020)
In this work, the nitrogen conversion factor in eggs Coturnix coturnix L. (Japanese quail), was determined. 850 eggs of Coturnix coturnix L. were analyzed, the maximum precipita-tion and extraction pH was determined by the Kjeldahl meth-od, at different acidic and basic pH. The protein conversion factors found for white and yolk were 6.33 and 6.30 respec-tively. These results justify its consumption compared to other food sources, high in protein in the human diet. © 2020, Venezuelan Society of Pharmacology and Clinical and Therapeutic Pharmacology. All rights reserved.